Clinical Document Architecture (CDA) Generation and Integration for Health Data Exchange based on Cloud Computing: A Survey - Jadhav, Komal R; Patil, Nitin N (International Journal of Computer Sciences and Engineering, 2019)
The Health level seven developed Clinical Document Architecture (CDA) is a core document that supports XMLbased mark-up commonplace that is used to specify the structure, linguistics, and encryption of a clinical document like a discharge outline or progress note for the aim of exchange between totally different hospitals. A CDA document is a set of the complete information object that may embody text, images, sound, and alternative transmission content. CDA will hold any reasonably clinical information that enclosed in every patient’s anamnesis like discharge outline following patient’s care history & physical specialist reports like those for medical imaging or pathology. Electronic Health Record helps improve patient safety and quality of care; however, it's the necessity of interoperability between health data exchange at completely different hospitals. CDA document generation and integration Open API service supported cloud computing, through that hospital's area allowed to handily generate CDA documents whereas not having to buy proprietary code software. The CDA document integration system integrates multiple CDA documents per patient into one CDA document and doctor and patients can browse the clinical information in chronological order. In this, the CDA document generation and integration depend on cloud computing and so the service is gettable in Open API. Developers using totally different platforms thus can use this system to increase ability. It providing security to the CDA document and unique identity (id) is generated and given to the patients for avoiding the interchanging and duplication of medical reports. Every detail in CDA Document is Encrypted and stored in the Database. All Details in CDA Document is secured utilizing different Security Algorithms.